Optimization of Dissolved Oil Separation for Produced Water Analysis - Khor, Ee-Huey; Samyudia, Yudi (National University of Singapore, 2010)
In this study, membrane filtration was utilized for an improved produced water analysis. Different types of membrane and operating conditions were explored in the dissolved oil separation and the concentration of oils-in-water was analysed using GC-MSD. Optmization of the membrane separation was performed using the Response Surface Methodology (RSM) D-optimal design to obtain optimum operating conditions and type of membranes. Analysis of variance (ANOVA) results reveal that the first-order model is sufficient to determine process parameters which have the significant impact on the separation process. Optimized operating parameters for the dissolved oil separation by membrane filtration was then verified experimentally.